You and your toddler - Stoker, Jenny (You and your child series (Karnac Books), 2005)
A central theme of this book is the gradual process of separation between parents and toddlers and the growth of autonomy in them all. Jenny Stoker has written with clarity, sympathy and warmth about the multiple problems children face in their toddler years and she has addressed the parents with immense empathy. Stoker manages to convey complex concepts and arguments in a lucid and simple style that all readers will find most helpful. Part of the new Your and Your Child Series.